Safety and immunogenicity of the novel H4:IC31 tuberculosis vaccine candidate in BCG-vaccinated adults: Two phase I dose escalation trials. Issue 12 (14th March 2017) - Norrby, Maria; Vesikari, Timo; Lindqvist, Lars; Maeurer, Markus; Ahmed, Raija; Mahdavifar, Shahnaz; Bennett, Sean; McClain, J. Bruce; Shepherd, Barbara M.; Li, Daner; Hokey, David A.; Kromann, Ingrid; et al.
Highlights: H4:IC31 vaccination was well tolerated with an acceptable safety profile. H4:IC31 vaccination elicited persistent antigen-specific CD4+ T cell responses. H4:IC31 triggered T cell expansion, IFNγ production and multifunctional Th1 cells. Optimal antigen-adjuvant doses were 5, 15, or 50 μg of H4 plus 500 nmol of IC31. Abstract: Background: Novel vaccine strategies are required to provide protective immunity in tuberculosis (TB) and prevent development of active disease. We investigated the safety and immunogenicity of a novel TB vaccine candidate, H4:IC31 (AERAS-404) that is composed of a fusion protein of M. tuberculosis antigens Ag85B and TB10.4 combined with an IC31® adjuvant. Methods: BCG-vaccinated healthy subjects were immunized with various antigen (5, 15, 50, 150 μg) and adjuvant (0, 100, 500 nmol) doses of the H4:IC31 vaccine (n = 106) or placebo (n = 18) in two randomized, double-blind, placebo-controlled phase I studies conducted in a low TB endemic setting in Sweden and Finland. The subjects were followed for adverse events and CD4 + T cell responses. Results: H4:IC31 vaccination was well tolerated with a safety profile consisting of mostly mild to moderate self-limited injection site pain, myalgia, arthralgia, fever and post-vaccination inflammatory reaction at the screening tuberculin skin test injection site. The H4:IC31 vaccine elicited antigen-specific CD4 + T cell proliferation and cytokine production that persisted 18 weeks after the last vaccination. CD4 + T cell expansion, IFN-γ production and multifunctional CD4 + Th1 responses were most prominent after two doses of H4:IC31 containing 5, 15, or 50 μg of H4 in combination with the 500 nmol IC31 adjuvant dose. Conclusions: The novel TB vaccine candidate, H4:IC31, demonstrated an acceptable safety profile and was immunogenic, capable of triggering multifunctional CD4 + T cell responses in previously BCG-vaccinated healthy individuals. These dose-escalation trials provided evidence that the optimal antigen-adjuvant dose combinations are 5, 15, or 50 μg of H4 and 500 nmol of IC31. Trial registration: ClinicalTrials.gov, NCT02066428 andNCT02074956 .